2022
DOI: 10.1039/d2dt00868h
|View full text |Cite
|
Sign up to set email alerts
|

Fluorinated 2,6-bis(arylimino)pyridyl iron complexes targeting bimodal dispersive polyethylenes: probing chain termination pathways via a combined experimental and DFT study

Abstract: The fluorinated 2,6-bis(arylimino)pyridyl iron (II) complexes, [2-[CMeN{2,4-{(4-FC6H4)2CH}2-6-F}]-6-(CMeNAr)C5H3N]FeCl2 (Ar = 2,6-Me2C6H3 Fe1, 2,6-Et2C6H3 Fe2, 2,6-iPr2C6H3 Fe3, 2,4,6-Me3C6H2 Fe4, and 2,6-Et2-4-MeC6H2 Fe5) and [2-[CMeN{2-{(4-FC6H4)2CH}-4-{(C6H5)CHAr’}-6-F}]-6-(CMeN(2,6-iPr2C6H3))C5H3N] FeCl2 (Ar’ = 3-(4-FC6H4)2CH}2-4-NH2-5-FC6H2 Fe6), being verified with...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 97 publications
2
16
0
Order By: Relevance
“…Evidently, the latter observation highlights the involvement of β-H elimination to metal or monomer during chain termination [24]. Moreover, by considering the integral ratio of vinyl H b to methyl chain-end H f (1/18.82) [29,37,38], the molar ratio of the unsaturated polymer chain to the saturated polymer chain can be determined as 0.379 (see SI), a value that implies the additional presence of a fully saturated polymer in line with chain transfer to aluminum being also operational [4,5]. Further support for these assignments was provided by the 13 C NMR spectrum, which reveals a high-intensity peak around δ 29.43 ppm, which corresponds to the -(CH 2 ) n -repeat unit, along with lower intensity peaks at δ 13.72, 22.38, and 31.66 ppm for an n-propyl end-group and weaker downfield peaks at δ 113.85 and 138.78 ppm for a terminal vinyl group (Figure 10) [24].…”
Section: Structural Analysis Of the Polyethylenementioning
confidence: 88%
“…Evidently, the latter observation highlights the involvement of β-H elimination to metal or monomer during chain termination [24]. Moreover, by considering the integral ratio of vinyl H b to methyl chain-end H f (1/18.82) [29,37,38], the molar ratio of the unsaturated polymer chain to the saturated polymer chain can be determined as 0.379 (see SI), a value that implies the additional presence of a fully saturated polymer in line with chain transfer to aluminum being also operational [4,5]. Further support for these assignments was provided by the 13 C NMR spectrum, which reveals a high-intensity peak around δ 29.43 ppm, which corresponds to the -(CH 2 ) n -repeat unit, along with lower intensity peaks at δ 13.72, 22.38, and 31.66 ppm for an n-propyl end-group and weaker downfield peaks at δ 113.85 and 138.78 ppm for a terminal vinyl group (Figure 10) [24].…”
Section: Structural Analysis Of the Polyethylenementioning
confidence: 88%
“…Kwon and Sun studied the reaction mechanism of ethylene polymerization by 1 H/ 13 C Nuclear Magnetic Resonance (NMR) and Density Functional Theory (DFT). [62][63][64] It was found that β-H transfer to aluminum and β-H elimination was the main chain termination pathway, while there also occurred β-H transfer to metal/monomer. There is no difference in the kinetic behavior of β-H transfer to metal and to the monomer, both were proportional to the first square of monomer concentration, and produced vinyl-terminated PE.…”
Section: Effect Of Ligand Structure On Chain Transfermentioning
confidence: 99%
“…Kwon and Sun studied the reaction mechanism of ethylene polymerization by 1 H/ 13 C Nuclear Magnetic Resonance (NMR) and Density Functional Theory (DFT) [62–64] . It was found that β ‐H transfer to aluminum and β ‐H elimination was the main chain termination pathway, while there also occurred β ‐H transfer to metal/monomer.…”
Section: Mechanistic Generalizationsmentioning
confidence: 99%
See 2 more Smart Citations